Skeletal Regeneration by Mesenchymal Stem Cells: What Else? - Andrades´-Gómez, José Antonio; Claros-Gil, Silvia; Jiménez-Palomo, Pedro; López-Puerta, José María; Zamora-Navas, Plácido; Guerado-Parra, Enrique; Monleón-Pradas, Manuel; Araque, María Carmen; Becerra-Ratia, José (InTech, 2011)
When regenerative medicine started several years ago, the main goal was for the implanted cells to directly participate in the reconstruction of the damaged tissue. But now, after the reported paracrine effects in several MSCs therapies we know that MSCs, far from building those tissues, they exert immunomodulatory functions, secreting, in addition, several bioactive molecules that inhibit apoptosis and scarring at sites of injury, and stimulate angiogenesis and mitosis of tissue-specific progenitors. These actions have been found either when the implanted MSCs coming from BM or adipose derived in adherent cell cultures or when themononuclear fraction of BM was infused. We cannot predict the extent of the paracrine effect, immunomodulatory, or if the effective replenishment of differentiated cells can be assigned, in each case, to the MSCs, or whether these effects have some degree of integration between them. We cannot even know if all those effects can influence the surrounding tissue positively during regeneration, but perhaps negatively towards the pathogenesis of cancer and metastasis. For now, we can only say that in many cases, these actions have a certain synergy to the purpose they claim. In the future, in might be useful to know the responsibility of each action in the regenerative process in order to control it appropriately. All this indicates the necessity to highlight again the importance of a tight control over the stem cell culture method in order to define the cell products for transplantation properly, according to the specific functional outcome sought.
Keywords: Células madre; Mesenchymal stem cells